Penta Helix Support Capability Towards The Performance Of Bkkbn Representatives Of North Sumatera Province (Case Study Of Acceleration Of Stunting Reduction In Medan City - Heri Pranata Satria; Kiki Farida Farene; Wilchan Robain (International Journal of Economics, Business and Innovation Research, 2025)
This research looks at how Penta Helix affects the work of the BKKBN in North Sumatra Province to speed up the reduction of stunting in Medan City. This quantitative study involved 103 BKKBN employees, with data analyzed using SmartPLS SEM. The results show that the roles of government, academics, business people, community, and social media directly have a positive and significant effect on BKKBN performance and the acceleration of stunting reduction. Indirectly, only the role of government and social media shows a significant effect on performance through stunting acceleration as an intervening variable. This study emphasizes the importance of government and social media in supporting BKKBN performance, while the role of academics, businesspeople, and communities needs to be further optimized. The results of this study help BKKBN come up with a Penta Helix-based plan to make the stunting reduction acceleration program work better.